A hybrid Neuro-Fuzzy - P.I. speed controller for B.L.D.C. enriched with an integral steady state error eliminator - Mansouri, M.; Kaboli, S. H. A.; Ahmadian, J.; Selvaraj, J. (2012 IEEE International Conference on Control System, Computing and Engineering, 2012)
This paper is subject to present a hybrid Neuro-Fuzzy (N.F.) - P.I. fed Controller for controlling the speed of B.L.D.C. (Brush Less D.C.) motors to evolve the drives controlling performance at both transient and steady state conditions by considering a paralleled robust integral S.S.E.E. (Steady State Error Eliminator) to enrich the whole controlling process. In the presented hybrid system, P.I. N.F.C. is the main controller loop while the paralleled integral S.S.E.E. controller reimburses the steady state errors. The presented B.L.D.C. drive contains the capabilities of quick tracking, small steady state error and high stability despite of all load and parameter variations. MATLAB simulation results depict the impressiveness of the presented controlling system.